Cophecheilus bamen, a new genus and species of labeonine fishes (Teleostei: Cyprinidae) from South China - Zhu, Yu; Zhang, E; Zhang, Ming; Han, Yao-Quan (Zootaxa, 2011)
A new garrain genus and species are described from a tributary of the Zuo-River of the Pearl River drainage in Guangxi Province, South China. Cophecheilus, new genus, is separated from all other Asian garrains by its uniquely modified oromandibular morphology; i.e., rostral cap with a shallow, arched, subdistal depression extending almost the full length of its ventral margin; upper lip greatly reduced to a thin membranous fold medially adnate to the upper jaw, but reflected slightly from its distal margin, and laterally produced into a frenum connecting the upper jaw with the lower lip. The new species, Cophecheilus bamen, has an inconspicuous longitudinal black stripe extending along each side of the body.